Emerging energy applications of two-dimensional layered materials - Late, Dattatray J.; Rout, Chandra Sekhar; Chakravarty, Disha; Ratha, Satyajit (Canadian Chemical Transactions, 2015)
Atomically thin semiconducting transition metal dichalcogenides (TMDCs) layered materials have recently been emerged as an exciting area of research due to accessibility for easy synthesis using various chemical and physical methods. These two-dimensional (2D) layered materials with single layer have direct and wide band gap due to which, they are more suitable for nanoelectronics and optoelectronics device applications. Here, we present a review of the energy related aspects of atomically thin layered materials like MoS2, WS2, MoSe2, WSe2, InSe, GaSe, GaTe, MoTe2, WTe2 etc. for supercapacitor, solar cell, lithium ion battery and water splitting application. By significantly assessing various materials and comparing their performances with challenging technology, the advantages and disadvantages of this promising area of energy materials are recognized, which may provide guidelines for future progress.

Enhanced field emission performance of NiMoO4 nanosheets by tuning the phase - Bankar, Prashant K.; Ratha, Satyajit; More, Mahendra A.; Late, Dattatray J.; Rout, Chandra Sekhar (Applied Surface Science, 2017)
In this paper we report, large scale synthesis of a and beta-NiMoO4 by a facile hydrothermal method and we observed that urea plays important role on the growth of beta-NiMoO4 nanosheets. We have also carried out field emission (FE) investigations of alpha and beta-NiMoO4 at a base pressure of similar to 1 x 10(-8) mbar. The obtained turn-on field at emission current density of 1 mu A/cm(2) for beta-NiMoO4 nanosheets and alpha-NiMoO4 is 1.3V/mu m and 2.2V/mu m respectively were observed. The maximum field emission current density of 1.006 mA/cm(2) at an applied electric field of 2.7V/mu m was achieved for beta-NiMoO4 nanosheets. Furthermore, we found that the beta-NiMoO4 nanosheets possess good field emission performance compared to alpha-NiMoO4. The results indicate that NiMoO4 can be used as a promising material in FE applications with possibility of tuning field emission performance by controlling the phase. (C) 2017 Elsevier B.V. All rights reserved.

Efficient bifunctional reactivity of K-doped CrO(OH) nanosheets: exploiting the combined role of Cr(iii) and surface -OH groups in tandem catalysis - Vernekar, Dnyanesh; Ratha, Satyajit; Rode, Chandrashekhar; Jagadeesan, Dinesh (Catalysis Science & Technology, 2019)
This work reports the bifunctional catalytic activity of layered K-doped alpha-CrO(OH). The combined action of the redox active Cr(III) and the surface hydroxyl groups was efficiently used to carry out 2-3 oxidation reactions in tandem followed by condensation/coupling reactions in one pot. Oxidation of benzyl alcohol followed by Knoevenagel condensation or coupling reactions forming C-C and C-N linkages in one pot is demonstrated. The catalyst has been characterized using XRD, IR, TGA, CO2-TPD, cyclic voltammetry, XPS and microscopic techniques to gain insight into the nature of active sites. The role of O- and O2- on the CrO(OH) catalyst in the bifunctional activity was studied using analytical techniques. Recyclability and leaching tests confirmed that K-alpha-CrO(OH) is a stable and environmentally safe catalyst.